PEDAGOGICAL AND PSYCHOLOGICAL CONDITIONS FOR FORMING AN INCLUSIVE ENVIRONMENT IN HIGHER EDUCATION (Scientific journal of the Fergana State University, 2026)
This article analyzes the pedagogical and psychological aspects of creating an inclusive environment in higher education institutions. The study highlights the importance of a learner-centered approach, positive teacher–student communication, empathy, and tolerance as key factors in establishing inclusion. Pedagogical conditions such as curriculum adaptation, flexible teaching strategies, and the development of teachers’ inclusive competencies are emphasized. Psychologically, the article focuses on the formation of a positive educational climate, emotional support for students, and the promotion of cooperation and mutual respect among participants in the educational process.